Variación genética en un ensayo de progenies de Pinus pringlei Shaw Ex Sargent procedentes de árboles superiores en producción de resina - Fabián Plesníková, Irenka (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
The state of Michoacán ranks first in resin production in Mexico, nevertheless, there are no breeding programs focused on increasing the volume of resin production. A first attempt to assess the genetic variation and the genetic control of 33 families of half–sib families from trees that were selected as good resin producers is being made by the National Union of Resin Tappers (NURT), in México. The Union has recently established three half-sib progeny trails of Pringle ́s Pine trees. These pine trees are endemic to Mexico and produce the highest volume of resin per tree on average. The first trail was established in the plant nursery Ferreira-Yunnan and there were measured two variables: height and stem diameter at two and four months after sown. The results of the measurements indicate that there were significant differences among the families (P=0.0001) in all evaluated traits. The contribution of the variance of the families to the total variance was lower regarding height than regarding diameter (σ2FAM%≤7.27; σ2FAM%=12.06). The genetic control was low at individual level (h2i≤0.29) and from relatively low to relatively high among the mean of families (h2f≤0.74), but higher in diameter (h2i=0.48; h2f=0.89). The regression analysis showed a relationship between the additive variance of the offsprings and the phenotypic characters of the parents (0.20≤r2≤0.43). The regression parameters were positive and significant. In the trails established in field there were assessed also two growth traits, height and diameter at 0, 2, 4, and 24 months after the plantation. The first trail, El Encinal, Tzitzio, Michoacán (Site 1) was established at an altitude of 2075 meters above sea level and the second one, La Calera, Hidalgo, Michoacán (Site 2) at 2479 meters.

Michoacán ocupa el primer lugar en producción de resina en México, sin embargo, no existen programas de mejoramiento genético enfocados a mejorar la producción. Para evaluar la variación y el control genético de 33 familias de medios hermanos procedentes de árboles de Pinus pringlei señalados como buenos productores de resina en Michoacán, México, la Unión Nacional de Resineros (UNR) estableció dos ensayos de progenies en campo. La planta producida en vivero se estableció como un ensayo de progenies completamente al azar en el vivero Ferreira-Yunnan, se encontraron diferencias significativas entre las familias (P=0.0001) en las variables evaluadas: altura, a los dos y cuatro meses, y diámetro, a los cuatro meses de edad. La aportación de la varianza de familia a la varianza total fue más baja en altura que en diámetro (?2FAM%?7.27; ?2FAM%=12.06). El control genético fue bajo a nivel individual (h2i?0.29) y de relativamente bajo a relativamente alto a nivel de medias de familias (h2f?0.74), pero más alto en el diámetro (h2i=0.48; h2f=0.89). El análisis de regresión mostró relación entre la varianza aditiva de las progenies con caracteres fenotípicos de los padres (0.20?r2?0.43) y los parámetros de regresión fueron positivos y significativos. En los ensayos establecidos en campo se evaluó la altura (ALT) y el diámetro (DIA) a las edades de 0, 2, 4 y 24 meses después de la plantación. El primer ensayo de campo se estableció a 2075 msnm en El Encinal, Tzitzio, Michoacán (Sitio 1) y el segundo a 2479 msnm en La Calera, Hidalgo, Michoacán (Sitio 2).
Instituto de Investigaciones Agropecuarias y Forestales. Maestría en Producción Agropecuaria
Keywords: info:eu-repo/classification/cti/6; IIAF-M-2014-0318; Heredabilidad; Selección temprana; Mejoramiento genético; Especies resineras; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6560